COMPUTER PRESENTATIONS USED IN LESSONS - RŮŽIČKA, Evžen (Trends in education, 2009)
Technical media used in lessons have changed a lot dutiny last twenty years. The biggest change was digitizing and computerization. It helped to Berger and easier presentation of subject matter and also for interactivity. It also helped production of tutorial material itself. To represent information with usage of electronic media, it is necessity today. Every presentation hat it's object and purpose which is important for the creator. Presentation is not just for transfer of information. Very important is comprehensive impression. Logica and well arranged sorting of every constituent which grip lookers on. This article should help teachers to orientace in this problematic to set up the basic principles of production of good presentations. There are mistakes, which creator can't do in creation of presentation.
Keywords: Computer; computer presentations; curriculum; trachet; student.